Effect of Oral Pilocarpine in Treating Severe Dry Eye in Patients With Sjögren Syndrome. Issue 2 (March 2015) - Kawakita, Tetsuya; Shimmura, Shigeto; Tsubota, Kazuo
Abstract : Purpose: The aim of this study is to evaluate the efficacy and safety of oral pilocarpine in treating severe dry eye unresponsive to conventional conservative treatment in patients with Sjögren syndrome. Design: A prospective study. Methods: Oral doses of pilocarpine were administered for at least 3 months to patients with Sjögren syndrome complicated by established dry eye of great severity unresponsive to conventional conservative treatment. Results: Subjective eye symptoms (dry eye sensation and eye pain), fluorescein staining scores, rose Bengal staining scores, and tear film breakup time measurements improved significantly after 1 month and 3 months of oral treatment with pilocarpine, whereas no significant improvement was noted in Schirmer I testing. Conclusions: Oral administration of pilocarpine was useful in treating severe dry eye unresponsive to conventional conservative treatment in patients with Sjögren syndrome from the standpoint of efficacy and safety. Thus, we conclude that oral pilocarpine is effective as a new option in treating severe dry eye.